Alveolar-capillary endocytosis and trafficking in acute lung injury and acute respiratory distress syndrome - Kryvenko, Vitalii; Vadász, István (Frontiers in Immunology, 2024)
Acute respiratory distress syndrome (ARDS) is associated with high morbidity and mortality but lacks specific therapeutic options. Diverse endocytic processes play a key role in all phases of acute lung injury (ALI), including the initial insult, development of respiratory failure due to alveolar flooding, as a consequence of altered alveolar-capillary barrier function, as well as in the resolution or deleterious remodeling after injury. In particular, clathrin-, caveolae-, endophilin-and glycosylphosphatidyl inositol-anchored protein-mediated endocytosis, as well as, macropinocytosis and phagocytosis have been implicated in the setting of acute lung damage. This manuscript reviews our current understanding of these endocytic pathways and subsequent intracellular trafficking in various phases of ALI, and also aims to identify potential therapeutic targets for patients with ARDS.